1992
DOI: 10.1007/bf00189427
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of bovine milk antibody against Escherichia coli in a mouse indigenous infection model

Abstract: A skim-milk fraction and a whey-protein concentrate (WPC) fraction were prepared from the cows that had been immunized with E. coli isolated from the mouse intestine. The antibacterial effect of these fractions against E. coli was examined. They contained antibody with a high affinity for E. coli strain 48, a representative strain in the mouse intestine, which is composed of a large amount of IgG and smaller amounts of IgA and IgM. Although these fractions showed no bactericidal or bacteriostatic activity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…One explanation could be that bovine immune milk contains a low-molecular-weight factor which prevents the migration of leucocytes from the circulation to the joint, thus reducing active synovitis [55]. The specific antibacterial effect ofbovine immune milk is thought to be antibody-mediated [56,57], but judging from animal studies the promotion ofthe intestine's immunological defence mechanisms may also be important [58,59]. In our study,no clinical effect was achieved with any dietary therapy.…”
Section: Concentration Oftnf-qt and Ct-l-antitrypsin In Faecesmentioning
confidence: 59%
“…One explanation could be that bovine immune milk contains a low-molecular-weight factor which prevents the migration of leucocytes from the circulation to the joint, thus reducing active synovitis [55]. The specific antibacterial effect ofbovine immune milk is thought to be antibody-mediated [56,57], but judging from animal studies the promotion ofthe intestine's immunological defence mechanisms may also be important [58,59]. In our study,no clinical effect was achieved with any dietary therapy.…”
Section: Concentration Oftnf-qt and Ct-l-antitrypsin In Faecesmentioning
confidence: 59%
“…This kind of milk is characterized by higher amounts of immunoglobulins specific to these gut bacteria. As we previously reported, immune milk-administration protected mice from opportunistic infection induced by 5FU and irradiation [14,15]. It improved autoimmune diseases assessed by survival rate, proteinuria and anti-DNA Abs in autoimmune disease-prone mice (NZBxNZW F1 mice) [16] and it also delayed age-related impairment of T cell responses [17].…”
Section: Introductionmentioning
confidence: 83%
“…We previously reported that immune milk could protect mice from indigenous infection induced by 5FU or irradiation, which damage intestinal epithelium and bone marrow, resulting in increased permeabilty and impaired host defense mechanism [15]. Immune milk may directly inhibit the invading pathogens in indigenous infection but also enhance local Th1 response which is most important for host defense against bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…An antibody-enriched whey protein concentrate (WPC), prepared by ultrafiltration of whey isolated from milk secreted by cows immunized with Clostridium difficile, was found to help prevent relapse when given orally to patients with C. difficile diarrhoea (van Dissel et al, 2005). Nomoto et al (1992) assessed the antibacterial effect of a skim milk fraction and WPC obtained from cows immunized with E. coli isolated from mouse intestine. Both fractions opsonized E. coli in vitro, and the opsonization by WPC increased uptake of bacteria by mouse liver macrophages in vivo.…”
Section: Introductionmentioning
confidence: 99%